Validación del proceso de fabricación de una forma farmacéutica líquida antiséptica tópica en laboratorios Remo S.A.S (2018)
The objective of this work is to validate the manufacturing process for Metaclor, Solution in Remo SAS Laboratories, based mainly on the FDA guidelines and resolution 1160 of the Ministry of Health and Social Protection of the Republic of Colombia, since It is very important to carry out a validation for this product in the company, not only for regulatory compliance but also for manufacturing costs reduction. Initially, an analysis of the product's background was made, obtaining valuable information for the diagnosis of the process, mainly master formula, equipment, facilities, critical and personal support systems, and from the diagnosis corrective actions were established in order to correct the non-compliance and start the validation process. For this validation it is necessary to begin with the evaluation of equipment, the qualification verification of critical support systems and analytical methodologies. After qualifying the equipment, the parameters of validation and critical parameters were defined by the analysis of cause and effect AMEF, and the sampling plan, finally the critical parameters were controlled during the production process of Metaclor ® and the statistical analysis resulting in the process being validated since the reproduction of the product is stable.